2009
DOI: 10.1186/1475-2859-8-27
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting plasmid production in Escherichia coli from a resource allocation standpoint

Abstract: BackgroundPlasmids are being reconsidered as viable vector alternatives to viruses for gene therapies and vaccines because they are safer, non-toxic, and simpler to produce. Accordingly, there has been renewed interest in the production of plasmid DNA itself as the therapeutic end-product of a bioprocess. Improvement to the best current yields and productivities of such emerging processes would help ensure economic feasibility on the industrial scale. Our goal, therefore, was to develop a stoichiometric model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…This huge increase seems to be caused by one, more or a combination of all effects: (i) the decrease in metabolic load and consequently the increased availability of metabolic precursors, resulting from deletion of the constitutively expressed nptII gene, (ii) the decrease of plasmid size and (iii) the increase in pDNA replication rate. This increase in specific plasmid yield is in accordance with a recent publication based on stoichiometric modelling of E. coli (Cunningham et al, 2009a). Although some therapeutic plasmids might be larger due to introns or multiple genes, the effect of decreased size is expected to be the same, in fact might even be more pronounced due to increased availability of metabolic precursors available for plasmid replication.…”
Section: Specific Pdna Content Is Increased With Plasmids Lacking Thesupporting
confidence: 85%
“…This huge increase seems to be caused by one, more or a combination of all effects: (i) the decrease in metabolic load and consequently the increased availability of metabolic precursors, resulting from deletion of the constitutively expressed nptII gene, (ii) the decrease of plasmid size and (iii) the increase in pDNA replication rate. This increase in specific plasmid yield is in accordance with a recent publication based on stoichiometric modelling of E. coli (Cunningham et al, 2009a). Although some therapeutic plasmids might be larger due to introns or multiple genes, the effect of decreased size is expected to be the same, in fact might even be more pronounced due to increased availability of metabolic precursors available for plasmid replication.…”
Section: Specific Pdna Content Is Increased With Plasmids Lacking Thesupporting
confidence: 85%
“…Interestingly, previous studies have indicated that constitutive expression of antibiotic resistance markers negatively affects host cells and in fact marker accumulation up to levels as high as 20% of total cellular protein29 and even inclusion body formation have been reported23. This imposes a metabolic load on host cells and it has been shown that its elimination can improve process performance, namely for plasmid production processes23.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is expected to impose a reduced metabolic burden on host cells due to the small sizes of the toxin (100 amino acids) and anti-toxin (90 amino acids) as well as the regulated expression of these (toxin production only in the absence of anti-toxin)252627. In contrast, the relatively large antibiotic-resistance proteins (β-lactamase: 263 amino acids + 23 amino acid signal sequence; aminoglycoside 3′-phosphotransferase: 271 amino acids) are constitutively expressed from the pET expression vectors and indeed have already been shown to have a deleterious effect on host cells242829.…”
mentioning
confidence: 99%
“…To test the inducible cell lysis system, we first introduced the genetic circuits L1, L2, L3, L12, L13, and L123 into strain Ec(Ri) on plasmids pSB1K3(FRTL1), pSB1K3(FRTL2), pSB1K3(FRTL3), pSB1K3(FRTL12), pSB1K3(FRTL13), and pSB1K3(FRTL123), respectively. Integration of genetic circuits into the chromosome is preferable to their maintenance on the plasmids [40, 41], therefore, in the next step we also integrated L1, L2, L3, L12, L13, and L123 into the chromosome of the strain Ec(Ri). The correct assemblies of lysis genes on plasmids and the chromosomally integrated genetic circuits were verified by diagnostic PCR with flanking primers (S1 Fig and S1 Table) and sequencing.…”
Section: Resultsmentioning
confidence: 99%